2015
DOI: 10.1089/dia.2015.0043
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Evaluation of Four Blood Glucose Monitoring Systems in Unaltered Blood Samples in the Low Glycemic Range and Blood Samples in the Concentration Range Defined by ISO 15197

Abstract: The investigated SMBG systems showed a significant variation of accuracy (measured by MARD), especially with higher MARD values in the low glycemic range. The selected comparison method had an impact on the MARD and therefore on the apparent accuracy of the SMBG systems. Sufficient measurement accuracy in the low glycemic range is required to enable users to react adequately to hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
2
33
0
1
Order By: Relevance
“…6,7,18 Noteworthy comparative studies reported good performance of CXT-BGMS when ISO 15197:2013 accuracy limits were applied. 16,17,19 In a recent multicenter study conducted in 21 hospitals under routine conditions using 2100 leftover blood samples, 20 CXT-BGMS results were remarkably congruent with the present data. The ISO accuracy limits and CEG results similarities corroborate the generalizability of the performance data of the CXT-BGMS in different hospital environments.…”
Section: Discussionsupporting
confidence: 88%
“…6,7,18 Noteworthy comparative studies reported good performance of CXT-BGMS when ISO 15197:2013 accuracy limits were applied. 16,17,19 In a recent multicenter study conducted in 21 hospitals under routine conditions using 2100 leftover blood samples, 20 CXT-BGMS results were remarkably congruent with the present data. The ISO accuracy limits and CEG results similarities corroborate the generalizability of the performance data of the CXT-BGMS in different hospital environments.…”
Section: Discussionsupporting
confidence: 88%
“…Several published studies have compared BGM brands and models by name during headto-head testing (56,57,136,(145)(146)(147)(148). For clinicians and consumers, MARD provides an excellent measure of accuracy and precision when evaluating a BGM (134).…”
Section: Iso Standardsmentioning
confidence: 99%
“…Accuracy of the systems was also analyzed by calculating mean absolute relative deviations, which is presented in a current publication. 8 The results of the bias analysis and regression analysis are shown in Table 4. Regarding the results obtained by using the manufacturers' comparison method, the relative bias of individual lots ranged from -6.2% (system 3) to +4.7% (system 2).…”
Section: Resultsmentioning
confidence: 99%